THE USE VIRTUAL YOUTUBERS (VTUBER) IN INFORMATION DISSEMINATION EFFORTS BY GOVERNEMENT INSTITUTION - Ahmad Hanif; Annisa Fajriyah (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2026)
Information dissemination is one of the primary activities carried out by various institutions, particularly those in the information services sector. The Meteorology, Climatology, and Geophysics Agency is a government agency that regularly disseminates information on climate, weather, and natural disasters, and has been innovating in its information dissemination methods. Having maintained a YouTube channel since 2017, this agency began innovating by using digital characters—known as virtual YouTubers (VTubers)—in 2024. Based on observations of its channel, the number of viewers accessing information presented by these digital characters tends to be higher compared to content without them. These virtual YouTubers have become a unique attraction for the public and align with the digital culture of young people. This is one of the key motivations behind this study. Additionally, this research aims to understand how the public responds to the information dissemination innovations implemented by the government agency, in this case the BMKG Gowa, when using digital characters as its medium. This study examines the public’s reception, understanding, and evaluation of the information dissemination conducted by the BMKG Gowa. The research method employed was quantitative, involving the collection of responses from 397 participants. Data analysis was based on the theory of information dissemination strategies, which encompasses the recipient, source, information content, context, and medium. These five factors serve as the primary indicators for measuring information dissemination in this study. The results of this study indicate that information dissemination using virtual YouTubers is well-received and positively evaluated by a significant portion of the public. Furthermore, the use of virtual YouTubers does not affect the public’s level of understanding regarding the information presented. The public remains able to clearly understand and trust the accuracy and relevance of the information provided.